2009
DOI: 10.1158/1535-7163.mct-09-0273
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXC receptor 4–mediated glioma tumor tracking by bone marrow–derived neural progenitor/stem cells

Abstract: Malignant gliomas manifest frequent tumor recurrence after surgical resection and/or other treatment because of their nature of invasiveness and dissemination. The recognized brain tumor-tracking property of neural progenitor/stem cells opened the possibility of targeting malignant brain tumors using neural progenitor/stem cells. We and others have previously shown that fetal neural progenitor/stem cells can be used to deliver therapeutic molecules to brain tumors. Our recent work has further shown that gene d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The CXCL12/CXCR4 axis is involved in several aspects of tumor progression including angiogenesis, metastasis, and survival (1,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The bone marrow microenvironment facilitates the survival, differentiation, and proliferation of normal hematopoietic cells, malignant hematopoietic cells, and epithelial tumor cell bone metastasis.…”
Section: Cxcr4 and Cancermentioning
confidence: 99%
“…The CXCL12/CXCR4 axis is involved in several aspects of tumor progression including angiogenesis, metastasis, and survival (1,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The bone marrow microenvironment facilitates the survival, differentiation, and proliferation of normal hematopoietic cells, malignant hematopoietic cells, and epithelial tumor cell bone metastasis.…”
Section: Cxcr4 and Cancermentioning
confidence: 99%
“…from the subventricular zone (SVZ) lining the lateral ventricles or from the corpus callosum, migrate toward experimental brain tumors (Assanah et al, 2006(Assanah et al, , 2009Chirasani et al, 2010;Glass et al, 2005;Walzlein et al, 2008). NPCs home in to pathologic brain tissue and possibly also to tumors due to expression of CXCR4 (Kokovay et al, 2010;Xu et al, 2009). The association of endogenous NPCs with glioblastomas may have been overlooked for many years, since it is only abundant in the young brain and since special animal models are necessary to distinguish glioblastoma cells from NPCs.…”
Section: The Interaction Of Glioblastomas With Neural Precursor Cellsmentioning
confidence: 99%
“…It has previously been characterized that HSCs are recruited to intracranial glioma via tumor-secreted CXCL12 21,22 which is the ligand for CXCR4, a receptor characteristic of HSCs. 23,24 Studies have demonstrated that CXCR4 blockade inhibits bone marrowderived progenitor cell migration to glioma, indicating that CXCR4 is required for their chemotaxis to tumor.…”
Section: E994374-6mentioning
confidence: 99%
“…23,24 Studies have demonstrated that CXCR4 blockade inhibits bone marrowderived progenitor cell migration to glioma, indicating that CXCR4 is required for their chemotaxis to tumor. 21 It has been suggested that HSC-derived pericytes may be recruited by tumors to contribute to tumor vasculature. 25 This intracranial recruitment of HSCs is further increased by radiation and the hypoxic environment in the brain.…”
Section: E994374-6mentioning
confidence: 99%